A survey on impulsive noise modeling. - Torres Gómez, Jorge (Telemática, 2017)
Impulsive noise is an undesirable signal from the communications channel that corrupts the transmitted signal in communications systems. Example of such a systems are Digital Television, Power Line Communications and Underwater Acoustic Communications in which the transmitted signals are more affected by this type of noise than by the typical AWGN noise. The current article summarizes several studies on impulsive noise from an statistical point of view. In this concern a variety of models are presented analytically and the main characteristics are described through the use of graphical representations. Furthermore, some ideas for future research field are also discussed.